Structure and Magnetic Properties of Sr2NaOsO6 - Thakur, Gohil S.; Felser, Claudia; Jansen, Martin (European Journal of Inorganic Chemistry, 2020)
Sr2NaOsO6, an ordered double perovskite, was obtained by solid-state synthesis. The compound crystallizes in a monoclinic cell [P21/n, a = 5.7043(1) Å, b = 5.7828(1) Å, c = 8.0816(2) Å; β = 90.01(2)°] and develops long-range antiferromagnetic order at ≈ 17 K with strong canting generating a tiny spontaneous moment of 0.06 µB/Os ion. A fit of the high temperature susceptibility data according to a modified Curie–Weiss law revealed a small effective paramagnetic moment of 0.7 µB/Os, which underlines the substantial effect of spin-orbit coupling in 5d oxides. A broad instead of a sharp lambda anomaly in specific heat data suggests frustration and strong magnetic disorder at the osmium lattice.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Canted antiferromagnets; Magnetic properties; Perovskite phases; Spin-orbit coupling